Milk fermented with Lactococcus lactis KLDS4.0325 alleviates folate status in deficient mice. Issue 5 (13th May 2020) - Jiao, Wenshu; Wang, Song; Guan, Jiaqi; Shi, Jialu; Evivie, Smith Etareri; Yan, Fenfen; Li, Na; Chen, Junliang; Li, Bailiang; Huo, Guicheng
Abstract : This study proved that milk fermented with L. lactis KLDS4.0325 can alleviate the folate status in deficient mice by animal experiment. Abstract : Folate is an essential B vitamin and its deficiency is common in many parts of the world. Natural folate produced by microorganisms may be an alternative to chemically synthesized folic acid (FA) as a dietary supplement. Previously, two lactic acid bacteria (LAB) strains, a high folate-producing Lactococcus lactis subsp. lactis KLDS4.0325 and a weak folate-producing Lactococcus lactis subsp. lactis KLDS4.0613, were identified. The aim of this study was to evaluate the effect of milk fermented with L. lactis KLDS4.0325 (folate-enriched fermented milk, FEFM) in alleviating folate deficiency status using murine folate deficiency models. In addition, the link between gut microbiota diversity and folate levels in mice was investigated. Results showed that FEFM increased FA and 5-methyltetrahydrofolate (5-MTHF) concentrations in the whole blood and liver, and decreased plasma homocysteine (Hcy) levels. 16S rDNA sequence analysis also revealed that the supplementation of FEFM (containing 0.6 μg mL −1 folate) and 0.6 μg d −1 FA (FEFM + LFA) significantly improved the poor status of the gut microbiota composition caused by folate deficiency, and the effect was better than that with 1.2 μg d −1 FA (HFA) supplementation. Our findings show that FEFM can be used as a folate-fortified food to alleviate folate deficiency effectively. In addition, it may be considered as a partial or total replacement for synthetic FA.